Budaya Melayu Pattani dalam Kajian Profetik - Siti Aisah; Mawi Khusni Albar (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2020)
This Abstract study aims to examine the Malay culture brought by Pattani students, Southern Thailand at IAIN Purwokerto. This research study is based on the characteristics of Malay culture from the prophetic perspective or following the prophet’s sunnah. Data collection in this research is in the form of Pattani Malay culture forms which are grouped based on subjective and objective aspects that develop in the community. Then analyzed using prophetic theory that develops education based on cultural criticism. The results showed that Pattani students applied several Malay cultures including: Islamic socializing culture, Islamic veiled culture, Malay-style Islamic dress culture, and several Islamic traditions carried out in the celebration of Islamic holidays (commemoration of the feast, the celebration of the birthday of the Prophet Muhammad, and commemoration of ma’a al-hijrah). The Malay cultures that Pattani students apply are cultures that breathe Islam, so all activities in these activities are based on Islamic law, which is in accordance with the Qur’an and as-Sunnah. So that the culture is able to realize the Islamic character that can be developed in Islamic education. Penelitian ini bertujuan untuk mengkaji budaya Melayu yang dibawa oleh mahasiswa Pattani, Thailand Selatan di IAIN Purwokerto. Kajian penelitian ini berdasarkan ciri khas kebudayaan Melayu dalam perspektif profetik atau mengikuti sunnah nabi. Pengumpulan data dalam penelitian ini berupa bentuk-bentuk budaya Melayu Pattani yang dikelompokkan berdasarkan aspek subjektif dan objektif yang berkembang di masyarakat. Kemudian dianalisis menggunakan teori profetik yang mengembangkan pendidikan berdasarkan kritis budaya. Hasil penelitian menunjukkan bah- wa mahasiswa Pattani menerapkan beberapa budaya Melayu di antaranya: budaya bergaul islami, budaya berjilbab islami, budaya berbusana islami khas Melayu, dan beberapa tradisi Islam yang dilaksanakan dalam pe- ringatan hari besar Islam (peringatan hari raya, peringatan maulid Nabi Muhammad saw, dan peringatan ma’a al-hijrah). Budaya-budaya Melayu yang mahasiswa Pattani terapkan merupakan budaya yang bernafaskan Islam, maka seluruh aktivitas dalam kegiatan tersebut berlandaskan pada hukum Islam, yaitu sesuai dengan al-Qur’an dan as-Sunnah. Dari budaya tersebut mampu mewujudkan karakter islami yang dapat dikembangkan dalam pendidikan Islam.